The role of OD practitioners in developing corporations' capacity to practice corporate citizenship: A sociomaterial case study. Issue 5 (2014) - ,
Abstract : Purpose – This study aims to analyze how organization development (OD) practitioners develop corporate citizenship for the purpose of increasing their organization's capacity to practice corporate citizenship. Research shows that very few corporations have the organizational capacity to practice corporate citizenship. Evidence exists that ever more corporations adopt programs of corporate citizenship development to increase this capacity. However, there still is a general lack of a strategic understanding of how corporate citizenship development occurs. The potential of OD frameworks and tools for developing corporate citizenship have been highlighted. Nevertheless, how OD practitioners develop corporate citizenship has not been studied empirically so far.Design/methodology/approach – A sociomaterial case study design was used. The work of six OD practitioners when developing corporate citizenship in one of the largest pharmaceutical corporations was studied over several months, based on interviews, observations and document analyses.Findings – The findings presented offer model practices of corporate citizenship development, in the form of five core strategies and five core behaviors that increase an organization's capacity to practice corporate citizenship.Research limitations/implications – With this study, the notion of corporate citizenship development has become established as a distinct research area. The study might encourage further research in this important niche area.Practical implications – The findings have direct practical implications for at least seven different stakeholder groups.Originality/value – The findings shed new light on both the epistemological and practical foundations of the concept of corporate citizenship, and hint to a new role of the fields of OD and human resource development in the twenty‐first century.